Enhancing Self-Regulated Learning in Distance Education through SQ3R and Concept Mapping: Supporting SDG 4 on Quality Education - Eko Kuswanti; Pesi Suryani; Melisa Arisanty; Sri Sukatmi (Postgraduate, University of Mataram, 2026)
This study examines the effectiveness of a dual-strategy intervention—SQ3R and concept mapping—in enhancing students’ comprehension and self-regulated learning (SRL) in an online distance learning context at Universitas Terbuka, Indonesia, contributing to SDG 4 (Quality Education). Using an explanatory sequential mixed-methods design, quantitative data were collected from 1.652 students through pretest–posttest measures in a one-semester course in the social sciences, followed by interviews with selected students and two instructors. Results indicate a statistically significant improvement in posttest scores (p < 0.001), although the effect size is small (d = 0.24). The strongest gains occurred in reading comprehension (SQ3R), with moderate improvements in concept mapping, while SRL gains remained limited. Qualitative findings suggest that students developed better reading structure, organization, and confidence; however, these did not fully translate into sustained metacognitive behaviors such as time management and reflective learning. This indicates that the intervention effectively improved cognitive and organizational skills but had limited short-term impact on deeper SRL habits. The study highlights the need for sustained scaffolding to develop SRL in distance education and supports the integration of structured learning strategies to improve learner autonomy.